Bedload transport and dune bedforms characteristics in sand-bed rivers supplying a retreating beach of the northern Adriatic Sea (Italy) - S. Cilli; P. Billi; L. Schippa; E. Grottoli; P. Ciavola (Journal of Hydrology: Regional Studies, 2021)
Study Region: The coast of the Emilia-Romagna Region in northern Italy consists of about 210 km of sandy beaches that have been attracting tourists for decades. Since the 1980s, erosion processes resulted in a remarkable beach retreat, notwithstanding the construction of several protections works. Study Focus: In 2005–2006 and 2017–2020, 30 floods of two small rivers feeding the beaches of Ravenna, Fiumi Uniti and Savio, were monitored and bedload was measured with a Helly-Smith sampler. Riverbed bathymetric surveys were carried out after some selected floods to investigate the occurrence and geometry of alluvial bedforms.The dune migration method was also used to calculate bedload. Results provided by this method are very encouraging. New Hydrological insights for the Region: To the authors knowledge, this field investigation on the bedload transport of small coastal rivers is the first one of this kind in the Adriatic and provides the regional land managers with a useful tool to predict the bedload yield for future scientifically based interventions, and hopefully successful, beach protection works.The bedload data indicate a higher variability of bedload for discharges lower than bankfull flow, whereas a stronger control of discharge is evident for larger floods. Though the bedload of the study rivers proved to be higher than in the largest river of the Region, it resulted rather low and witnesses sediment supply-limited conditions.